Clavipectoral fascia block with superficial cervical plexus block versus interscalene brachial plexus block with superficial cervical plexus block for postoperative analgesia in clavicle surgeries - Divakar SR; Shivakumar G; Chilla A; Konda RKR (Journal of Medical and Scientific Research)
Background: Traditionally, General Anesthesia (GA) has been preferred for clavicle fracture fixation, but recent advancements favor ultrasound-guided regional nerve blocks, offering cost-effectiveness, superior postoperative analgesia, and fewer GA-related adverse effects. The study aimed to compare the duration of post operative analgesia in superficial cervical plexus block with interscalene block (ISB + SCPB) versus superficial cervical plexus block with clavipectoral fascia block (CPB + SCPB) in patients posted for midpoint clavicle surgery.